A first study comparing preservation of a ready-to-eat soup under pressure (hyperbaric storage) at 25°C and 30°C with refrigeration - Moreira, S. A. (2022)
Hyperbaric storage (HS), storage under pressure at 25°C and 30°C, of a ready-to-eat (RTE) soup was studied and compared with refrigeration. Soup was stored at different time (4 and 8 h), temperature (4°C, 25°C, and 30°C), and pressure (0.1, 100, and 150 MPa) conditions, to compare microbial loads and physicochemical parameters. HS resulted in similar (microbial growth inhibition) to better (microbial inactivation) results compared to refrigeration, leading to equal and lower microbial loads, respectively, at the end of storage. Lower/higher pressure (100 vs. 150 MPa) and shorter/longer storage times (4 vs. 8 h) resulted in more pronounced microbial growth inhibition/microbial inactivation. Aerobic mesophiles showed less susceptibility to HS, compared to Enterobacteriaceae and yeast and molds. HS maintained generally the physicochemical parameters at values similar to refrigeration. Thus, HS with no need for temperature control throughout storage and so basically energetically costless, is a potential alternative to refrigeration.